Causes of circadian rhythm disorders and methods of their treatment - Machaj, Damian; Mazurek, Aleksandra; Cyboran, Katarzyna; Kuc, Monika; Machaj, Dominik (Journal of Education, Health and Sport, 2022)
The circadian rhythm is the main biological rhythm to which man is subject.During the day periods of activity and sleep, eating habits, body temperature, secretion of certain hormones and frequency of urination all change.In anatomical terms, the biological clock is located in the suprachiasmatic nuclei in the hypothalamus[3].The most important factor in the circadian rhythm is sunlight.They are particularly vulnerable to disturbances of the circadian rhythmschool students and shift workers,however, please note thatphenomenonthiscan occur in anyone.The consequences of circadian rhythm disorders include: reduced work efficiency, reduced social contacts, mood disorders, depression, obesity or metabolic diseases[1]. Mainandcausesanddisturbances of the circadian rhythmis reduced exposure to natural sunlight[1,2].Studies have shown that the biological rhythm may be disturbed by: the aging process [3],incorrect concentrationsuch hormones asmelatoninandand cortisol[4,8-27], symptoms of various diseases such as schizophrenia and medications taken[6],extension of the circadian cycle[7,28]and factors such associal life, time spent using multimedia devices, putting off homeworkby the studentslate evening hours, decreased parental control, increased frequency of anxiety disorders,non-compliance with the rules of sleep hygiene and consumption of caffeine-containing products[7,28,29, 30]. The treatment of circadian rhythm disorders is primarily based on the patient's adherence to the rules of sleep hygiene.The use of phototherapy is also an effective method. In case ofthe ineffectiveness of the above methodsdrug treatment may be considered. Melatonin is the drug of choice.In the case of treatment with melatonin, the correct time of administration is crucialand his dose.Pharmacotherapy with hypnotic drugs has a modest, short-term efficacy and should be used inlast resort[7.31]